Effect of whole body cryotherapy interventions on health-related quality of life in fibromyalgia patients: A randomized controlled trial. (February 2018) - Vitenet, M.; Tubez, F.; Marreiro, A.; Polidori, G.; Taiar, R.; Legrand, F.; Boyer, F.C.
Highlights: Whole body cryotherapy can improve health-reported quality of life in fibromyalgia patients. This study offers a perspective on the impact of Cryotherapy on health. Patients in the WBC group reported significantly improved for health-reported quality of life. Abstract: Introduction: Although fibromyalgia syndrome (SFM) affects 2–4 percent of adults, research has not identified a preferred therapeutic option for patients worldwide yet. Based on recent findings, it can be expected that whole body cryotherapy can improve health-reported quality of life by alleviating the symptoms of musculoskeletal pain and fatigue. Objective: Our aim was to determine whether whole body cryotherapy only can result in improved perceived health and quality of life in fibromyalgia patients. Methods: 24 patients with fibromyalgia diagnosis were randomized into 2 groups (n = 11 in the whole body cryotherapy group, n = 13 in the control group). In the whole body cryotherapy group, 10 sessions of whole body cryotherapy were performed (in addition to usual care) in a standard cryotherapy room over a duration of 8 days. Subjects in the control group did not change anything in their everyday activities. Quality of life was assessed just before and one month after treatment. Results: Compared with the control group, patients in the whole body cryotherapy group reported significantly improved for health-reported quality of life. These effects lasted for at least one month following intervention. Conclusion: Based on these findings, whole body cryotherapy can be recommended as an effective clinically adjuvant approach in the improvement of health-related quality of life in fibromyalgia patients.